HISTOGRAPHIC ANALYSIS OF INFRARED THERMOGRAMS IN THE FIELD OF THERMAL ENGINEERING - BENKŐ, Imre (Periodica Polytechnica Mechanical Engineering, 1994)
Computerized evaluation of infrared images opens new vistas for infrared thermogrammetry (IR-TGM). While it extends our earlier knowledge regarding temperature field analysis, it requires deeper understanding of relations of thermal phenomena and also more intuitive thermotechnical skills for image processing. Examples from diverse areas, e.g. energy saving, thermal defectometry, electrotechnics are quoted and practical applications of IR-TGM in thermal physics of buildings are discussed. The thermal phenomena themselves are illustrated by IR thermograms, while temperature distributions are analysed by histograms.